The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c4ta05982d
|View full text |Cite
|
Sign up to set email alerts
|

Hollow carbon spheres with encapsulated germanium as an anode material for lithium ion batteries

Abstract: A novel composite consisting of hollow carbon spheres with encapsulated germanium (Ge@HCS) was synthesized by introducing a germanium precursor into the porous-structured hollow carbon spheres. The carbon spheres not only function as a scaffold to hold the germanium and thus maintain the structural integrity of the composite, but also increase the electrical conductivity. The voids and vacancies that are formed after the reduction of germanium dioxide to germanium provide free space for accommodating the volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 25 publications
0
38
0
3
Order By: Relevance
“…Structural design with surface coating modification: a) Schematic illustration of self-assembled germanium/carbon nanostructures and TEM images of the nanostructures corresponding to each synthetic step. [23] Copyright 2014, Royal Society of Chemistry. [22] Copyright 2012, John Wiley and Sons.…”
Section: Surface Coating Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural design with surface coating modification: a) Schematic illustration of self-assembled germanium/carbon nanostructures and TEM images of the nanostructures corresponding to each synthetic step. [23] Copyright 2014, Royal Society of Chemistry. [22] Copyright 2012, John Wiley and Sons.…”
Section: Surface Coating Modificationmentioning
confidence: 99%
“…To alleviate or eliminate the adverse influence of these problems, some strategies have been applied to optimize the electrochemical properties, including structural modification, [11,[13][14][15][16][17][18][19][20] modification by surface coating, [21][22][23][24] forming germaniumbased alloys, [25][26][27] and forming binary [28][29][30][31][32][33] or ternary [34][35][36] germanium-based composites. Based on our previous studies and experience, we found that the complete and effectively surface coating on nanostructures with high structural robustness is vital to achieving good electrochemical performance in terms of high specific capacity, superior long-term cyclability, and good rate capability.…”
Section: Introductionmentioning
confidence: 99%
“…The rate capability and the capacity are becoming more important than ever in battery technology for application in hybrid or pure electric vehicles, which require higher specifications of energy density and power density. Among the lithium alloybased anode materials, Si has the highest specific capacity of 4200 mAh g -1 for Li 22 Si 5 , but the poorest electrical conductivity and lithium diffusivity. Accordingly, the Si anode only can cycle at a rather slow rate.…”
Section: Introductionmentioning
confidence: 99%
“…A high reversible capacity of 745 mA h g –1 at C/5 was shown by carbon‐coated Fe 3 O 4 nanospindles, and this was attributed to the facts that the carbon coating layers improved the electronic conductivity and protected the electrode materials from cracking and aggregation . The polymerization of resorcinol–formaldehyde (RF) prepared by a simple procedure with precise control has drawn attention in surface coating, as it can be further transformed into a carbon coating, as in Si@C, hollow carbon spheres with encapsulated germanium (Ge@HCS), and pitaya‐like Sn@C nanocomposites . These composite materials showed enhanced performance.…”
Section: Introductionmentioning
confidence: 99%